In Vitro Biodegradation Pattern of Collagen Matrices for Soft Tissue Augmentation - Cristina Vallecillo (Polymers, 2021)
Collagen matrices have become a great alternative to the use of connective tissue grafts for soft tissue augmentation procedures. One of the main problems with these matrices is their volume instability and rapid degradation. This study has been designed with the objective of examining the degradation of three matrices over time. For this purpose, pieces of 10 × 10 mm2 of Fibro-Gide, Mucograft and Mucoderm were submitted to three different degradation tests—(1) hydrolytic degradation in phosphate buffer solution (PBS); (2) enzyme resistance, using a 0.25% porcine trypsin solution; and (3) bacterial collagenase resistance (Clostridium histolyticum)—over different immersion periods of up to 50 days. Weight measurements were performed with an analytic microbalance. Thickness was measured with a digital caliper. A stereomicroscope was used to obtain the matrices’ images. ANOVA and Student–Newman–Keuls tests were used for mean comparisons (p < 0.05), except when analyzing differences between time-points within the same matrix and solution, where pair-wise comparisons were applied (p < 0.001). Fibro-Gide attained the highest resistance to all degradation challenges. The bacterial collagenase solution was shown to constitute the most aggressive test as all matrices presented 100% degradation before 14 days of storage.